MASJID PERAHU, JAKARTA SELATAN: KEUNIKAN MASJID PERAHU DAN WISATA RELIGI (1998-2010) - Khasanah, Alfiyyah Nur; Sulasman, Sulasman; Lestari, Fathia (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2021)
This paper contains history and also religious tour of the great mosque of Al-Munada Darussalam Baiturrahman in South Jakarta. In the Chronicles of the great mosque of Al-Munada Darussalam Baiturrahman stood in 1963 that was erected by KH. Qosim Abdurrahman Mashum and KH. Amen Abdurrahman. In the study the method of writing history goes through the four stages of heuristics, criticism, interpretation and histroriography. The great mosque of Al-Munada Darussalam Baiturrahman is also commonly known as the boat mosque, so it is said that makes the boat mosque a religious tour.